A preliminary randomized trial of the safety, tolerability, and clinical effects of hemp-derived cannabidiol in alcohol use disorder - Mueller, Raeghan L.; Hooper, Jake F.; Ellingson, Jarrod M.; Olsavsky, Aviva K.; Rzasa-Lynn, Rachael; Bryan, Angela D.; Bidwell, L. Cinnamon; Hutchison, Kent E. (Frontiers in Psychiatry, 2025)
IntroductionCannabidiol (CBD) has recently gained attention for its potential therapeutic effects in substance use disorders, including Alcohol Use Disorder (AUD). This study examined the potential therapeutic effects of commercially available products containing CBD with and without a small amount of tetrahydrocannabinol (THC) on alcohol use and craving among individuals with moderate to severe AUD.MethodsIn this feasibility study, a total of 44 participants were randomized to one of three conditions: full-spectrum CBD (n = 13, fsCBD - <0.3% THC), broad-spectrum CBD (n = 15, bsCBD – without THC), or placebo control (n = 16) for 8 weeks. The study was designed to assess the safety and tolerability of these treatments and to evaluate whether CBD demonstrated any clinical effects (Clinicaltrials.gov Identifier: NCT04873453; https://clinicaltrials.gov/study/NCT04873453). It was hypothesized that both CBD conditions would be well tolerated and would reduce drinking, alcohol dependence, and craving compared to placebo.ResultsAnalyses of attrition and side effect data indicated no significant differences across conditions, suggesting that both bsCBD and fsCBD were well tolerated. Individuals receiving fsCBD demonstrated reductions in craving but no reduction in drinks per drinking day.DiscussionIn this pilot study, safety profiles fsCBD and bsCBD were similar, and fsCBD was associated with a greater reduction in craving and AUD symptoms relative to both bsCBD and placebo. Future studies with larger sample sizes will be necessary to replicate and extend these findings by addressing the question of whether a small amount of THC may work synergistically with CBD.